2023
DOI: 10.1007/s10654-022-00938-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific contribution of contacts to transmission of SARS-CoV-2 in Germany

Abstract: Current estimates of pandemic SARS-CoV-2 spread in Germany using infectious disease models often do not use age-specific infection parameters and are not always based on age-specific contact matrices of the population. They also do usually not include setting- or pandemic phase-based information from epidemiological studies of reported cases and do not account for age-specific underdetection of reported cases. Here, we report likely pandemic spread using an age-structured model to understand the age- and setti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The main analysis omits the age group of children under 15 years as only 2.7% of cases, and a single death was observed in this group in the study period until May 2020. Later studies confirmed that the transmission activity in children was particularly low in the first wave in Germany: Seroprevalence surveys 45 found children 1 to 10 years old had particularly low levels of antibodies in measures taken in May 2020, and a transmission study using age‐specific contacts 46 found children to have little contribution in the first wave in Germany.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The main analysis omits the age group of children under 15 years as only 2.7% of cases, and a single death was observed in this group in the study period until May 2020. Later studies confirmed that the transmission activity in children was particularly low in the first wave in Germany: Seroprevalence surveys 45 found children 1 to 10 years old had particularly low levels of antibodies in measures taken in May 2020, and a transmission study using age‐specific contacts 46 found children to have little contribution in the first wave in Germany.…”
Section: Methodsmentioning
confidence: 97%
“…Recently, contact matrices for Germany during the first wave were used to model transmission 46 . A simulation study in Section 5 uses those contact matrices to investigate the model's performance in the presence of age importation.…”
Section: Methodsmentioning
confidence: 99%
“…The preliminary age-group related OD matrices have been published freely in [28]. Note that in this study age group related traffic has been recomputed by (10).…”
Section: Mobility and Contact Patternsmentioning
confidence: 99%
“…Over the last years, to predict SARS-CoV-2 development in Germany, contributions have been made by a variety of different approaches. Among these approaches are agent-based models [6,7], models based on ordinary differential equations (ODE) [8][9][10] or delay differential equations [11], advanced ODE-based models [12] using the linear chain trick [13] to waive the implicit assumption of exponentially distributed transition times, and in particular metapopulation or graph-ODE models [14].…”
Section: Introductionmentioning
confidence: 99%
“…These estimate the number of unreported cases with data from blood donations or estimation models, for example, but mainly refer to the rst waves of infection during the pandemic. [15][16][17] Therefore, the objective of this study was to estimate the rate of unreported SARS-CoV-2 infections in the population using test data from various indicators collected over a longer period and thus including multiple waves of infection.…”
Section: Introductionmentioning
confidence: 99%